2013
DOI: 10.1002/jcc.23282
|View full text |Cite
|
Sign up to set email alerts
|

Modeling peptide binding to anionic membrane pores

Abstract: Peptide-induced pore formation in membranes can be dissected into two steps: pore formation and peptide binding to the pore. A computational method is proposed to study the second step in anionic membranes. The electrostatic potential is obtained from numerical solutions to the Poisson-Boltzmann equation and is then used in conjunction with IMM1 (implicit membrane model 1). A double charge layer model is used to incorporate the effects of the membrane dipole potential. Inhomogeneity of the charge density in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 81 publications
(132 reference statements)
3
36
0
Order By: Relevance
“…Due to the fairly small size of the system, the effect of imposing proper structural restraints and then removing them in separate steps (see Figure 2) is relatively small (∼1 kcal/mol); the exception is observed at a low anionic lipid fraction, in which case the binding is weak, and thus it is important to properly treat the conformational flexibility of the peptide by following the protocol in Figure 2. The differential solvation PMF protocol used in previous work 34,40,41,60 (⟨ΔΔW slv ⟩ men column in Table 1) gives somewhat similar results to both BAR and the (un)binding PMF, although with notably larger statistical uncertainties (also see Figure S3 in the Supporting Information).…”
Section: Journal Of Chemical Theory and Computationsupporting
confidence: 70%
“…Due to the fairly small size of the system, the effect of imposing proper structural restraints and then removing them in separate steps (see Figure 2) is relatively small (∼1 kcal/mol); the exception is observed at a low anionic lipid fraction, in which case the binding is weak, and thus it is important to properly treat the conformational flexibility of the peptide by following the protocol in Figure 2. The differential solvation PMF protocol used in previous work 34,40,41,60 (⟨ΔΔW slv ⟩ men column in Table 1) gives somewhat similar results to both BAR and the (un)binding PMF, although with notably larger statistical uncertainties (also see Figure S3 in the Supporting Information).…”
Section: Journal Of Chemical Theory and Computationsupporting
confidence: 70%
“…(57) Other factors besides membrane affinity, such as membrane penetration depth or hydrophobic matching, may influence membrane disruption by peptides. (5860)…”
Section: Discussionmentioning
confidence: 99%
“…Three different models for peptidemembrane interaction are commonly used: barrel-stave, toroidal and carpet models [9][10][11]. It was suggested that collective behaviour of peptides can play a role in the bacterial membrane destruction [12][13][14][15][16][17][18][19]. For instance, using 31 P oriented solid-state NMR experiments it was found that at high peptide concentration alamethicin adopts a transmembrane conformation while the novicidin forms a toroidal pore in the membrane [16].…”
Section: Introductionmentioning
confidence: 98%